PENGARUH PERSONALITY, SENSE OF BELONGING DAN WORK CONFLICT TERHADAP PERFORMANCE KARYAWAN GEMILANG MANAGEMENT INDONESIA (GMI) BALI - Virgia Ratna Devi; Made Yudi Darmita (Universitas Triatma Mulya, 2026)
The purpose of this study is to understand the impact of employee perceptions, workplace conflict, and work-related stress. Gemilang Management Indonesia (GMI) Bali became the research location. other questionnaires, interviews, and documentation are the research data used in this study. The sample size used is the GMI Bali workforce, with a total sample size of 63 GMI employees. In this study, Descriptive statistical analysis, instrument analysis, analysis of classical assumptions, analysis of multiple line regression, f test, t test, and beta coefficient test are some of the techniques used for data analysis. According to the study's findings, the personality t-test had a t-value of 2.656 and a significance of 0.10, the sense of belonging t-value of 4.178 and a significance of 0.000, and the work conflict t-value of -4.104 and a significance of 0.000. With a ttable comparison of 1.671 and the conditions significance < 0.05, it is possible to conclude that the work conflict variable has a significant negative impact on employee performance, while the personality and sense of belonging variables have a positive and significant effect on employee performance. The three independent variables—personality, feeling of belonging, and work conflict—have a considerable impact on employee performance when taken together, as seen by the F test results, which show a F value of 39.767 > F table 2.76 and a significance value of 0.000 < 0.05. It may be concluded that the sense of belonging has a stronger impact on employee performance since the beta coefficient test findings indicate that this variable has the greatest value (0,930) when compared to the other variables.